menu
bartleby
search
close search
Hit Return to see all results

F(x)=(-x)3-x2-x+7 we are supposed to indicate the function value with f(1)+f(-1). I know the answer is 12 but am having issues reaching that in my work.

Question

F(x)=(-x)3-x2-x+7 we are supposed to indicate the function value with f(1)+f(-1). I know the answer is 12 but am having issues reaching that in my work.

check_circleAnswer
Step 1
The given equation is f(x)=-(x)3- x2-x+7.
in f(x)=-(x)3-x2-x7 to fin the value of f(-1)
Substitute x
f(-)-((-1)3(-))-(-1)+7
=(1)3 (1))7
3-117
=11-1
=10
Thus, the value of f(-1) =10
Substitute x 1 in f(x)=-(x)3- x2- x+7 to fin the value of f(1)
f(-1)(-0))3())-1)+7
=(-1)3(1)17
=-3-1-1+7
=-57
= 2
Thus, the value of f (1) = 2
help_outline

Image Transcriptionclose

The given equation is f(x)=-(x)3- x2-x+7. in f(x)=-(x)3-x2-x7 to fin the value of f(-1) Substitute x f(-)-((-1)3(-))-(-1)+7 =(1)3 (1))7 3-117 =11-1 =10 Thus, the value of f(-1) =10 Substitute x 1 in f(x)=-(x)3- x2- x+7 to fin the value of f(1) f(-1)(-0))3())-1)+7 =(-1)3(1)17 =-3-1-1+7 =-57 = 2 Thus, the value of f (1) = 2

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Our solutions are written by experts, many with advanced degrees, and available 24/7

See Solution
Tagged in

Math

Algebra

Polynomials

Sorry about that. What wasn’t helpful?